Legal-Social Analysis of the factors of domestic violence in Paraguay (Legal journal - Research in Legal and Social Sciences, 2024)
This research aims to identify the factors that contribute to the perpetration of this type of criminal act, starting with a brief overview of the concept of the victim, a description of their main characteristics, the social context in which it occurs most frequently, and the legal analysis that governs this situation. For this purpose, a qualitative approach was employed, using a nonexperimental, dogmatic-documentary design with a descriptive, cross-sectional scope, drawing on both national and foreign doctrine and regulations to highlight legal similarities and the direct social impact on family relationships. The findings determined the factors influencing the causation of this criminal act and concluded that, given its persistent nature, a thorough legal-social study is required to achieve solutions from both perspectives, aiming to significantly reduce the incidence of such cases. These are issues that necessarily affect the core of society, which is undoubtedly the family. It was concluded that the State should increase its efforts through its institutions to achieve substantial improvements in the current situation and reach an adequate standard of living that fosters harmonious family coexistence.
Keywords: domestic violence; family; procedure; legislation